Diagnostic accuracy for major depression in multiple sclerosis using self-report questionnaires - Fischer, Anja (Brain Behav, 2015)
OBJECTIVE: Multiple sclerosis and major depressive disorder frequently co-occur but depression often remains undiagnosed in this population. Self-rated depression questionnaires are a good option where clinician-based standardized diagnostics are not feasible. However, there is a paucity of data on diagnostic accuracy of self-report measures for depression in multiple sclerosis (MS). Moreover, head-to-head comparisons of common questionnaires are largely lacking. This could be particularly relevant for high-risk patients with depressive symptoms. Here, we compare the diagnostic accuracy of the Beck Depression Inventory (BDI) and 30-item version of the Inventory of Depressive Symptomatology Self-Rated (IDS-SR(30)) for major depressive disorder (MSS) against diagnosis by a structured clinical interview. METHODS: Patients reporting depressive symptoms completed the BDI, the IDS-SR(30) and underwent diagnostic assessment (Mini International Neuropsychiatric Interview, M.I.N.I.). Receiver-Operating Characteristic analyses were performed, providing error estimates and false-positive/negative rates of suggested thresholds. RESULTS: Data from n = 31 MS patients were available. BDI and IDS-SR(30) total score were significantly correlated (r = 0.82). The IDS-SR(30)total score, cognitive subscore, and BDI showed excellent to good accuracy (area under the curve (AUC) 0.86, 0.91, and 0.85, respectively). CONCLUSION: Both the IDS-SR(30) and the BDI are useful to quantify depressive symptoms showing good sensitivity and specificity. The IDS-SR(30) cognitive subscale may be useful as a screening tool and to quantify affective/cognitive depressive symptomatology.